2015
DOI: 10.1002/marc.201500495
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchically Structured Porous Poly(2‐oxazoline) Hydrogels

Abstract: A new method for fabricating hydrogels with intricate control over hierarchical 3D porosity using microfiber porogens is presented. Melt electrospinning writing of poly(ε-caprolactone) is used to create the sacrificial template leading to hierarchical structuring consisting of pores inside the denser poly(2-oxazoline) hydrogel mesh. This versatile approach provides new opportunities to create well-defined multilevel control over interconnected pores with diameters in the lower micrometer range inside hydrogels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…An alternative to MEW or electrospinning to create structured PAOx hydrogels is the use of sacrificial templating. Our group showed that precisely controlled microsized channels can be incorporated into PEtOx–ButenOx hydrogels by using a 3D printed sacrificial poly(ε‐caprolactone) fibrous structure created using MEW . This approach could be used to make hydrogel‐based microfluidic devices or tissue engineered constructs with vascular‐like features.…”
Section: Emerging Applicationsmentioning
confidence: 99%
“…An alternative to MEW or electrospinning to create structured PAOx hydrogels is the use of sacrificial templating. Our group showed that precisely controlled microsized channels can be incorporated into PEtOx–ButenOx hydrogels by using a 3D printed sacrificial poly(ε‐caprolactone) fibrous structure created using MEW . This approach could be used to make hydrogel‐based microfluidic devices or tissue engineered constructs with vascular‐like features.…”
Section: Emerging Applicationsmentioning
confidence: 99%
“…Nanofibrillar hydrogels are well-suited as a 3D cell culture scaffold due to their similarity to the extracellular matrix; when properly designed, synthetic hydrogels can mimic the physical and biological properties of in vivo cell environments [712]. β-hairpin hydrogels consist of peptides that fold into β-hairpin conformation and then undergo hydrophobic collapse and hydrogen bonding into nanofibrils with a hydrophobic core [13].…”
Section: Introductionmentioning
confidence: 99%
“…These characteristics have promoted the use of MEW as an ABM technique for the printing of 3D biomaterial-based porous constructs, termed as scaffolds, that can be populated with cells to guide cellular function [33][34][35]. For example, 3D poly(e-caprolactone) (PCL) fibrous scaffolds with lattice architecture and fiber diameters ranging from 0.8 to 40 lm have been printed via MEW [17,26,[36][37][38][39][40][41][42][43][44][45][46][47][48]. These studies have mainly targeted scaffold-guided tissue engineering (TE) applications, with the reported micron-scale scaffolds promoting cell viability and demonstrating cell-invasive and favorable mechanical properties.…”
Section: Governing Equations and Nondimensionalizationmentioning
confidence: 99%